2018
DOI: 10.1002/jmri.26282
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐guided treatment in the breast

Abstract: In the last decades, an increasing interest has developed towards non‐invasive breast lesion treatments, which offer advantages such as the lack of surgery‐related complications, better cosmetic outcomes, and less psychological distress. In addition, these treatments could be an option for patients with poor health who are not candidates for surgery. Non‐surgical ablation can be performed under magnetic resonance (MR) or ultrasound (US) guidance. US is cheaper and easily available, while contrast‐enhanced MR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
(139 reference statements)
1
13
0
1
Order By: Relevance
“…Simmons et al 7 published the results of a Phase II clinical trial (ACOSOG Z1072) on cryoablation of early stage breast tumors ⩽2.0 cm in diameter reporting an overall success rate of 75.9%, and when patients with multifocal disease were excluded, a 92% success rate. More recently, Pediconi et al 10 published a review of the use of ablation procedures (RFA, HiFu, Laser, and Cryo) using an magnetic resonance imaging (MRI) image guided approach and reported that “no serious complications were reported with these techniques and that these non-surgical approaches offer promise as a replacement to radical surgery when possible.” They also concluded that “further research utilizing these techniques should focus on the development of an even less invasive approach to breast neoplasms.” Finally, Pusceddu et al 18 recently reviewed the breast cancer cryoablation literature and concluded that “. .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simmons et al 7 published the results of a Phase II clinical trial (ACOSOG Z1072) on cryoablation of early stage breast tumors ⩽2.0 cm in diameter reporting an overall success rate of 75.9%, and when patients with multifocal disease were excluded, a 92% success rate. More recently, Pediconi et al 10 published a review of the use of ablation procedures (RFA, HiFu, Laser, and Cryo) using an magnetic resonance imaging (MRI) image guided approach and reported that “no serious complications were reported with these techniques and that these non-surgical approaches offer promise as a replacement to radical surgery when possible.” They also concluded that “further research utilizing these techniques should focus on the development of an even less invasive approach to breast neoplasms.” Finally, Pusceddu et al 18 recently reviewed the breast cancer cryoablation literature and concluded that “. .…”
Section: Introductionmentioning
confidence: 99%
“…With a continued rise in diagnosis and advances in biomarkers, the use of thermal ablation for pre-and metastatic breast cancer have experienced an increase in use and efficacy in the past 10 years. [6][7][8][9][10][11][12][13][14][15] Ablative techniques such as cryotherapy have been used for the treatment of solid tumors for over 100 years. 16,17 Thermal therapies include radiofrequency ablation (RFA), high-intensity focused ablation (HiFu), and cryoablation.…”
mentioning
confidence: 99%
“…Although preoperative breast MRI can provide more information for determining the surgical range with high sensitivity, some investigators do not recommend breast MRI as a diagnostic imaging modality for breast cancer. Moreover, the detection rate can vary widely (40-100%) [26][27][28][29][30][31]. Therefore, breast MRI requires an experienced radiologist who can accurately interpret the images and determine the degree of suspicion of background breast parenchyma and contralateral breast parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…It has widely been used for planning surgical treatment in selected patients with invasive breast cancer and DCIS, and for assessing response to neoadjuvant systemic therapy 40,41. After cryoablation treatment, damaged cancer cells stay located in the treated area, thus MRI may be the most accurate image tool for evaluating responses to cryoablation 6,34,42. Manenti et al reported a good correlation between MRI volume and histological samples size in their series of 80 patients submitted to either radiofrequency ablation or cryoablation and surgical removal of the tumor 34.…”
Section: Imaging Follow-up After Cryoablation Treatmentmentioning
confidence: 99%